PARTNER MODEL IMPLEMENTATION ANALYSIS IN EMPOWERING VANAME SHRIMP FARMERS (STUDY IN MUARA BATU DISTRICT) - Ti Aisyah; T.Alfiady; Ahmad Yani; Mauludi, Mauludi; Murniati, Murniati (International Journal of Social Science, 2024)
Empowerment of pond farmers is an important effort that must be done in terms of improving the economy of rural communities. Partnership is a mutually beneficial business partnership between pond farmers and partner companies accompanied by guidance and development by partner companies. However, the problem is that the management of shrimp ponds, especially panamy shrimp, is not always successful. Many pond farmers experience crop failure. In recent times more crops have failed than succeeded. For this, a local government response is needed to encourage pond farmers to build partners with various business entities in order to realize the resilience of their businesses. This study aims to analyze the application of the Partner Model in Empowering Paname Shrimp Farmers in Muar Batu District. It is hoped that this research can produce solutions in increasing the resilience of Vaname Shrimp Farms (Aspects of Capital, Human Resources, Infrastructure, Production and Marketing Aspects Study). The target of this research will be to contribute in reducing the risk of crop failure and be able to increase the success of the management of the panam shrimp pond business for the pond farming community in Muara Batu District. This study uses a qualitative approach with descriptive analysis research type. Data collection techniques were carried out by observation, interviews and documentation. The data analysis technique uses an interactive model through the stages of data reduction, data display, conclusion drawing and verification. The results show that the business partner model built by pond farmers in Muara Batu District tends to use the Mutualism Partnership model (mutualistic partnership) with partners expected to strengthen each other, and profitably can reduce problems. Several companies that have partnered with pond owners in Muara Batu sub-district include PT. CPP pattern of operational cooperation partnership (KSO), PT. CV Cherry, PT. Surya Windu Pertiwi, PT. Indonesia Evergeen Agriculture, PT. Intraco Agroindustry. The activities of business partners are in the aspect of increasing production in the field of feed, fry. Aspect of HR conducts training and provision of expert technicians. No partners have been built in the procurement of infrastructure and capital aspects